Design, synthesis and biological evaluation of glycosidase inhibitors in an anti-cancer setting - Glawar, AFG (2013)
The aim of the work described in this thesis was to explore the synthesis of glycosidase inhibitors and to evaluate their potential as anti-cancer agents. Glycosidases catalyze the fission of glycosidic bonds and are involved in vital biological functions. With regard to their potential for anti-cancer therapy, two glycosidases were identified: α-N-acetyl-galactosaminidase and β-N-acetyl-hexosaminidase. The former has been implicated in causing immunosuppression in advanced cancer patients by negating the effect of the macrophage activating factor (MAF), while the latter is secreted by invading cancer cells and hence associated with metastasis formation. The synthetic focus was on generating piperidine and azetidine iminosugars, carbohydrate mimetics with their endocylic oxygen replaced by nitrogen. Their structural similarity to carbohydrates make iminosugars excellent inhibitors of glycosidases. Following synthesis of a pipecolic amide, its previously reported potent β-N-acetyl-hexosaminidase inhibition was confirmed. This data, along with inhibition profiles of several pyrrolidines, allowed the generation of a molecular model for predicting activity of β-N-acetyl-hexosaminidase inhibitors. The model was used to select azetidines in the D/L-ribo and D-lyxo configuration as suitable candidates to be explored in novel chemical space, leading to the first synthesis of a fully unprotected 3-hydroxy-2-carboxy-azetidine. The potent α-N-acetyl-galactosamindase inhibitor 2-acetamido-1,2-dideoxy-D-galacto-nojirimycin (DGJNAc) was successfully derivatised via N-alkylation. Important structural discoveries with regard to glycosylation of vitamin D3-binding protein, the precursor of MAF, were made using MALDI mass-spectrometry. By comparing the enzymatic and cellular inhibition of N-alkylated derivatives of DGJNAc and a pyrrolidine the following generalization on iminosugar biodistribution was found: N-butylation promotes uptake into the cell/organelles, while hydrophilic side-chains restrict cellular access. An in vitro assay evaluating cancer cell invasion was devised and β-N-acetyl-hexoamindase inhibitors were shown to retard cell migration, including with the highly metastatic breast cancer cell line MDA-MB-231. Additive effects where found when the iminosugar was combined with a protease inhibitor, suggesting potential for future combination therapy.